Design for 3D printing : - Bernier, Samuel N. (Maker Media, 2015)
This book gives you the techniques to turn a product idea into a 3D model and a prototype. Focusing on free design software and affordable technologies, the exercises in this book are the perfect boost to any beginner looking to start designing for 3D printing.